1998
DOI: 10.1164/ajrccm.158.4.9710043
|View full text |Cite
|
Sign up to set email alerts
|

Salmeterol Prevents Aspirin-induced Attacks of Asthma and Interferes with Eicosanoid Metabolism

Abstract: We determined the effect of a long acting beta2-agonist, salmeterol, on aspirin-induced asthma (AIA) attacks and urinary release of eicosanoids in a double-blind, placebo-controlled, crossover study in 10 asthmatics sensitive to aspirin. The patients inhaled 50 microgram of salmeterol or placebo 15 min prior to a cumulative challenge with increasing doses of lysine-aspirin (L-ASA) (Part I), and before a single, predetermined dose of L-ASA that caused a 20% fall in FEV1 (PD20) (Part II). Salmeterol significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Previous studies had reported that levels of PGD 2 metabolites in urine, plasma, or BAL fluid either remain unchanged 24,33,47,4 , or increase modestly with aspirin challenges in subjects with AERD 48 . The differences between these and our data likely reflect differences in sampling, the heterogeneous nature of AERD 49 , and the variable proportions of subjects with the phenotype defined by Group II.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies had reported that levels of PGD 2 metabolites in urine, plasma, or BAL fluid either remain unchanged 24,33,47,4 , or increase modestly with aspirin challenges in subjects with AERD 48 . The differences between these and our data likely reflect differences in sampling, the heterogeneous nature of AERD 49 , and the variable proportions of subjects with the phenotype defined by Group II.…”
Section: Discussionmentioning
confidence: 97%
“…This model included four genotypes: B2ADR 46A>G, CCR3-520T>G, CysLTR1-634C>T, and FCER1B-109T>C. Of these four genes, the B2ADR 46A>G and CCR3-520T>G polymorphisms have been reported as being related to asthma [12][13][14] and the CysLTR1-634C>T and FCER1B-109T>C polymorphisms have been identified as significant genetic risk factors for developing AIA in the Korean population [7,23]. Moreover, B2ADR agonists (beta2 agonists and salmeterol) and CysLTR1 antagonists (montelukast and pranlukast) have been widely used to control asthma symptoms in the management of AIA patients [24,25]. Therefore, the best model suggested by MDR in this study is in agreement with the data from previous genetic association studies of AIA, which showed significant associations between SNPs and AIA in the Korean population.…”
Section: Discussionmentioning
confidence: 99%
“…Another pitfall that may produce false-negative aspirin provocation is indicated by observations that high doses of glucocorticosteroids may mask aspirin intolerance [203]. Moreover, it has been documented that treatment with antileukotrienes [96] and salmeterol [204] blunt the lysineaspirin induced airway response.…”
Section: Diagnostic Value Of Indirect Challengesmentioning
confidence: 99%